2023
DOI: 10.1007/s11845-023-03387-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aerobic exercise alone or combined with Mediterranean diet on dry eye in obese hypertensive elderly

Abstract: Background Lifestyle modification is a newly recommended complementary treatment for dry eye (DE) disorder. Objective To investigate the effect of a 6-month high-intensity interval aerobic exercise (HIIAE) (conducted 30 min, 3 times weekly) alone or combined with a caloric-restriction approach, the Mediterranean diet (MD), on DE parameters in obese hypertensive elderly. The design, settings, participants, and intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…This suggestion is consistent with a few human studies that showed a promising role for AE in the prevention or treatment of DE and DE-associated low quality of life ( Ismail et al, 2023 ; Kawashima et al, 2014b ; Sano et al, 2018 ), in addition to the evidence-based positive response of tear secretion to AE in diabetic rats ( Sano et al, 2014 ).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…This suggestion is consistent with a few human studies that showed a promising role for AE in the prevention or treatment of DE and DE-associated low quality of life ( Ismail et al, 2023 ; Kawashima et al, 2014b ; Sano et al, 2018 ), in addition to the evidence-based positive response of tear secretion to AE in diabetic rats ( Sano et al, 2014 ).…”
supporting
confidence: 90%
“…One treatment option for MeTs-associated DE may be aerobic exercise (AE), which is advised by healthcare nurses to improve OS, boost antioxidant status, and reduce systemic inflammation in MeTs patients. This is especially true given the ineffectiveness of DE medications in treating DE symptoms ( Ismail et al, 2023 ).…”
mentioning
confidence: 99%
“…In addition to this finding, Digenio et al (2009) reported that a high-frequency face-face lifestyle modification counselling showed significant improvements in high-density lipoprotein cholesterol and triglyceride levels, waist circumference, measures of quality of life and weight-related symptoms. Likewise, a six-month high-intensity interval aerobic exercise that was conducted for 30 min three times daily with a caloric restriction and the Mediterranean diet significantly reduced the BMI and blood pressure ( Ismail et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…To start the low-calorie diet, the value of BMR was subtracted from 500 kilocalories per day [ 13 ]. Besides fruits (such as peach, apple, pear, strawberries, plum, guava, and pineapple) and vegetables, macronutrients (20–30% fats, 10–15% proteins, and 55–65% carbohydrates) formed the 3-meal diet plan daily [ 13 , 14 ]. To monitor the adherence of psoriatic men with MeTS and ED to the introduced energy restriction program, the low-calorie diet was reviewed weekly through a face-to-face interview.…”
Section: Methodsmentioning
confidence: 99%